Feuerbach's Criticism of Hegel's Defamiliarized Man - شباني , منذر; عبد الإبراهيم , عبد الرحمن (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The Research discusses the types of defamiliarizing Man in Idealistic philosophy. It starts with tackling human condition within the model that is called Hegelian negation or 'negation relations' in which Man takes a stand against his/her own humanity. For, Man cannot actually fulfill unity and harmony within the system of the Absolute. In that system, Man is considered an attachment to existence, yet human nature is simultaneously emphasized. After that, the research discusses the concept of Being, viz. Man's Being within the philosophy of the Absolute, and this Being does not achieve its independence from that of the Absolute. All of this has directed human existence towards being under the influence of bereavement and externalization as Man's humanism is incapable of self-assertion. Feuerbach, at this particular point, equates Idealistic philosophy with the philosophy of the Absolute and theology.